1990
DOI: 10.1007/bf00371943
|View full text |Cite
|
Sign up to set email alerts
|

In vivo percutaneous absorption: a key role for stratum corneum/vehicle partitioning

Abstract: Percutaneous absorption of five compounds was studied in the hairless rat in vivo: benzoic acid, caffeine, hydrocortisone, inulin and thiourea. The results clearly demonstrate that, as with in vitro experiments, a steady-state flux can be achieved in vivo. This steady-state flux is strongly molecule dependent. Thus, the values for inulin and benzoic acid differ by a factor of about 40. In contrast, although the physicochemical properties of the studied compounds vary widely, their lag times were not significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Mom etasone furoate is strongly lipophilic, which seems to be associated with a high penetration rate [20]. The composition of different cream vehicles has previously been shown to in fluence the effect of topical steroids pro foundly [17], Although a direct correlation between lipophilicity (partition coefficient of solvent/water) and the permeability constant cannot always be established, there is an em pirically good correlation between these two parameters within the same class of com pounds. The partition coefficient (P) of mometasone furoate in octanol/water is (log P) = 3.8 and for betamethasone valerate (log P) = 3.6.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Mom etasone furoate is strongly lipophilic, which seems to be associated with a high penetration rate [20]. The composition of different cream vehicles has previously been shown to in fluence the effect of topical steroids pro foundly [17], Although a direct correlation between lipophilicity (partition coefficient of solvent/water) and the permeability constant cannot always be established, there is an em pirically good correlation between these two parameters within the same class of com pounds. The partition coefficient (P) of mometasone furoate in octanol/water is (log P) = 3.8 and for betamethasone valerate (log P) = 3.6.…”
Section: Discussionmentioning
confidence: 95%
“…The EEC classification of topical cortico steroid preparations is based on a series of dif ferent properties, mainly different chemical modifications of the steroid molecule [13,17], These may strongly affect the penetra tion, binding and biodegradation properties of the compounds. Also the composition of the vehicle has a substantial influence on the potency of topical preparations [14][15][16], Since the introduction of corticosteroids, chemical engineering has provided a series of optimized steroid molecules for topical prep arations [16,20], Mometasone furoate is a recently introduced synthetic corticosteroid in which the steroid nucleus is a 16-methyl analogue of beclomethasone with a 21 -chloro group and a novel (2') furoate 17-ester.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the minimal inhibitory concentration values (MIC100), defined as the lowest preservative concentration that prevented any discernible growth with respect to the control, relative to single parabens and to mixtures of PP and BP are reported in Table III. As already known from the literature (20), BP is more active than PP as a preservative. Furthermore, the associations of PP and BP show the same MIC value of BP alone.…”
Section: Antimicrobial Testsmentioning
confidence: 61%
“…This difference is considered to be the cause of the different percutaneous penetration of these drugs. Rougier et al 30) and Surber et al 31) have reported that the penetration flux value of a substance depends on its partition coefficient between stratum corneum and vehicle. The difference of percutaneous penetration among these four formulations may originate in the difference of their ingredients.…”
Section: Discussionmentioning
confidence: 99%